Release of an encrypted, highly potent ACE-inhibitory peptide by enzymatic hydrolysis of moth bean (Vigna aconitifolia) protein - Goyal, Nancy; Hajare, Sachin N.; Gautam, Satyendra (Frontiers in Nutrition, 2023)
Dietary approaches for the regulation of blood pressure is the need of the hour. Hence, identifying the foods possessing such activity is gaining importance. With this aim moth bean (Vigna aconitifolia), an underutilized pulse, was explored for the presence of antihypertensive activity in terms of angiotensin converting enzyme (ACE)-inhibition bioactivity. For this, defatted moth bean protein concentrate was hydrolyzed using different proteases including Alcalase, papain, and trypsin, to identify the enzyme producing highly potent ACE inhibitory peptides. Out of these proteases, Alcalase-derived hydrolysate showed the highest (~59%) ACE inhibition activity. Molecular weight based fractionation revealed that <1 kDa fraction possessed the highest ACE inhibitory activity. The active fraction (< 1kDa) was further subjected to ion-exchange chromatography followed by RP-HPLC to separate the peptides based on charge and hydrophobicity. LC-MS/MS analysis of the HPLC purified fraction showed the presence of about 45 peptides. Based on the bioinformatic analysis, 15 peptides were synthesized and evaluated for ACE inhibitory activity. Among these, a novel octapeptide FPPPKVIQ showed the highest ACE inhibitory activity (93.4%) with an IC50 of 0.24 µM. This peptide retained about 59% activity post gastrointestinal digestion simulation. A Dixon plot as well as docking studies revealed the uncompetitive inhibitory nature of this peptide with a Ki value of 0.81 µM. Molecular dynamic simulation studies till 100 ns ensured the stability of the ACE-peptide complex. Thus, present study identified a novel potent ACE inhibitory peptide from moth bean that can be incorporated in a functional dietary formulation for regulation of hypertension.